Managing the quality of seeds from cereal conditioned with effective microorganisms (EM) and red light (RL) - Agata Dziwulska-Hunek; Mariusz Szymanek; Jacek Dziwulski (Agronomy Science, 2022)
The study pertained to environmentally-friendly methods in the cultivation of cereal, and aimed to manage the quality of rye and triticale seeds and determine the impact of seed conditioning using effective microorganisms (EM), red light (RL), and a combination of the two (RL × EM) on the yield of grain and straw. Moreover, the seeds were sown into soil with and without EM conditioning, designated as 0 and PEM. The yield fluctuations depended mostly on the studied rye and triticale cultivars. The best effects we observed in soil without EM conditioning for Dańkowskie Złote rye and Moderato triticale. The increase in grain and straw yields was, respectively: 26% (RL), 31% (RL × EM), 40% (EM), and 17% (RL × EM), 23% (RL), 32% (EM) – Dańkowskie Złote, 27% (RL × EM), 44% (EM), 46% (RL), and 17% (RL × EM), 51% (EM), 78% (RL) – Moderato. In turn, seeds exposed to the experimental treatment and sown into soil containing EM produced reduced yields in both of the above cultivars. It is noteworthy that the conditioning methods employed in the field experiment can facilitate increased yields but most importantly contribute to the resilience of agrosystems and can therefore have environmental benefits. It is noteworthy that the conditioning methods employed in the field experiment can facilitate increased yields but most importantly contribute to the resilience of agrosystems and can therefore have environmental benefits.